Developing Collaboration Between Parents, Schools, and the Community to Improve the Quality of Education at Jurong Pande Public Elementary School - Irmayani Irmayani; Muhammad Iqbal; Didi Yudha Pranata (FKIP - Universitas Riau, 2026)
Educational quality improvement requires effective collaboration among schools, parents, and the community, especially in the era of educational transformation. This study was conducted to examine the conditions, implementation, and effectiveness of school family community collaboration in improving educational quality at Jurong Pande Public Elementary School. The research employed a mixed methods approach, combining quantitative and qualitative data. Quantitative data were collected through Likert scale questionnaires distributed to parents, teachers, and community members, while qualitative data were obtained through interviews, observations, and documentation. The results indicate that collaboration among parents, teachers, and the community is generally categorized as good to very good, particularly in aspects of communication, participation, and support. Observational findings confirm that collaborative activities are consistently implemented and integrated into school programs. Expert validation results show that the developed collaboration model is highly valid and feasible for implementation. The study concludes that structured, participatory, and sustainable collaboration among schools, parents, and communities contributes positively to improving academic performance, student character development, and the overall school environment. Future research may explore the application of this collaboration model in different educational contexts to strengthen its adaptability and sustainability.